The Contribution of Optimism toResilience of the Ex-Prostitutes in Undergoing Rehabilitation at the Andam Dewi Sukarami, Solok - Alhaitamy Alhaitamy; Netrawati Netrawati (Universitas Negeri Padang, 2021)
This research is based on optimism, which is an important thing that must be owned by every individual, because high optimism will make it easier for someone to develop themselves, because they believe in themselves and know their own strengths and weaknesses, therefore the Ex -Prostitutes who are undergoing rehabilitation must have high optimism to make it easier for them to increase their resilience and start a new life later. This study aims to determine the contribution of optimism of Ex-Prostitutes to their resilience in undergoing rehabilitation at PSKW Andam Dewi Sukarami Solok. The total sample in this study was 40 Ex-Prostitute who were undergoing rehabilitation. This type of research is descriptive correlational. Data were collected using an optimism questionnaire and a resilience questionnaire with a Likert scale model. The data were processed using the percentage technique and simple linear regression Adjusted R Square. The results of the data analysis of this study indicate that (1) the level of optimism possessed by the ex-Prostitutes is in the medium category with a percentage of 50%, (2) the resilience of the Ex-Prostitutes is in the high category with a percentage of 55%. (3) Based on the analysis of the coefficient of determination (Adjustale R Square), there is a contribution of 54.7% between the optimism of the Ex-Prostitutes for resilience and 45, the other% is influenced by other factors.